(untitled) (Journal of Rangpur Medical College, 2024)
Background: Hypothyroidism is a common endocrine disorder in our country and is associated with many biochemical abnormalities.Clinical data suggest that levothyroxine replacement therapy has beneficial effect on lipid profile. Objective: The present study intends to find out the effect of levothyroxine replacement therapy on lipid profile in hypothyroid patients. Methods: A prospective analytical study was done in Endocrinology Outpatient Department of Dhaka Medical college and Hospital, Dhaka from January 2022 to December 2022. A total of 30 newly diagnosed hypothyroid patients were included according to selection criteria. The patient’s demographic, past, present history and relevant data needed for the study were collected by face-to-face interview by using structured questionnaire. Baseline data of serum free thyroxine (FT4), thyroid stimulating hormone (TSH), fasting lipid profile, Blood pressure and clinical features of hypothyroidism were recorded in a data collection form during first visit and after 3 months follow up. All patients were treated with tablet levothyroxine and dose was adjusted 4-6 weekly till patients were biochemically euthyroid. Results: 30 hypothyroid patients were followed up for 3 months. There was significant improvement in hypothyroid symptoms after thyroxine replacement. The mean age of the patient was 35.40±11.52 years. Mean FT4 level was significantly increased from 8.06±3.78 to 16.40±3.95(p<0.001). There was significant reduction in mean TSH from 32.55±37.31 to 2.52±2.71(p<0.001). Mean Total cholesterol, TG, LDL-C level was significantly decreased from 193.27±41.69, 173.33±63.71, 119.58±40.11 to 177.80±38.17, 155.87±58.25, 103.07±26.25 (p=0.022, 0.044, 0.042) respectively, but HDL has decreased from 45.04±13.14mg/dl to 43.11±10.78 mg/dl (p=0.415) though not significantly. Conclusion: Thyroxine replacement therapy improves lipid profiles and enhances quality of life. Levothyroxine directly reduces TC, LDL-C, and TG levels but not HDL-C. J Rang Med Col. September 2024; Vol. 9, No. 2: 61-66